EFFORTS TO IMPROVE MASTERY OF INDONESIAN LANGUAGE VOCABULARY BY USING ANAGRAM GAMES (WORD WALL) IN GRADE IV ELEMENTARY SCHOOL MIN 1 MEDAN IN THE 2023/2024 ACADEMIC YEAR - Harahap, Nurindah Syahyanna Putri; Syamsuyurnita, Syamsuyurnita (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
The purpose of this study is to determine the increase in Indonesian vocabulary mastery by using the Anagram Game (Word Wall) in Elementary School Class VI MIN 1 Medan in the 2023/2024 academic year. This study uses PTK (Classroom Action Research). Data analysis is an activity after data from all respondents or other data sources are collected. The subjects and objects of this study were all 24 students in grade IV. This research procedure used Cycle I and Cycle II. The research instrument used a test. The data analysis technique uses three steps, namely: (1) Data reduction, (2) Data presentation, and (3) Drawing conclusions or verification. So from the explanation above, it can be concluded that Indonesian vocabulary can increase by using the anagram game (word wall) in Elementary School Class IV Min 1 Medan. The results of the study showed that the use of Wordwall was proven effective in improving the mastery of Indonesian vocabulary in grade IV Min 1 Medan students, as evidenced by an increase in the average test score of 173%. In addition to improving vocabulary mastery, Wordwall was also proven to be able to motivate students to learn more actively and improve their interpersonal skills through interaction in Indonesian. This study opens up opportunities for the development of more interactive and meaningful learning models for students. Wordwall, with its various features and ease of use, has the potential to be an effective learning tool in improving Indonesian language mastery at various levels of education.